2013
DOI: 10.1007/978-3-642-35999-6_10
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Arithmetic on Elliptic Curves over Fields of Characteristic Three

Abstract: Abstract. This paper presents new explicit formulae for the point doubling, tripling and addition for ordinary Weierstraß elliptic curves with a point of order 3 and their equivalent Hessian curves over finite fields of characteristic three. The cost of basic point operations is lower than that of all previously proposed ones. The new doubling, mixed addition and tripling formulae in projective coordinates require 3M + 2C, 8M + 1C + 1D and 4M + 4C + 1D respectively, where M, C and D is the cost of a field mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Since then, the elliptic curve cryptosystem has been invested in the field of public key cryptography because of its low bandwidth and small space storage requirements [3]- [6]. In the main operation of public key schemes, scalar multiplication can be accomplished using elliptic curves [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the elliptic curve cryptosystem has been invested in the field of public key cryptography because of its low bandwidth and small space storage requirements [3]- [6]. In the main operation of public key schemes, scalar multiplication can be accomplished using elliptic curves [7].…”
Section: Introductionmentioning
confidence: 99%
“…Twisted Hessian curves were used in [10] to provide a complete unified addition formula and improve efficiency for point doubling and tripling over fields of arbitrary characteristic. Other works that optimized arithmetic on (twisted) Hessian curves include [25][26][27]. Definition 1.…”
Section: Twisted Hessian Curvesmentioning
confidence: 99%
“…• The scaled projective coordinate system (X, Y, T ) was proposed in [4]. The affine coordinates (x, y) of a point P can be derived from its scaled projective coordinates (X, Y, T ) as x = X/bT and y = Y /bT .…”
Section: Curve Operationsmentioning
confidence: 99%
“…The complexities of the curve operations in each coordinate system are given in Table 2. Farashahi et al showed in [4] that the most advantageous coordinate system is the scaled projective system for curves admitting a point of order three. Smart and Westwood proved in [15] that these curves are isomorphic to curves given by a Weierstrass equation of the form…”
Section: Curve Operationsmentioning
confidence: 99%
See 1 more Smart Citation